Computational exploration of Casson fluid flow over a Riga-plate with variable chemical reaction and linear stratification - Loganathan, Parasuraman; Deepa, Krishnamurthy (Nonlinear Analysis: Modelling and Control, 2020)
Simulation of electro-magneto-hydrodynamic Casson fluid flow subject to cross stratification and variable chemical reaction is exemplified numerically. The model, which is governed by the system of partial differential equations, accomplishes the implicit finite difference solution. The variable chemical reaction enables the study to investigate an exponentially varying reaction rate along the stratified flow. Further, the mesh-contour plots impart the precise visualization of flow field in 3D and its projection as contour on XY -plane. The stronger chemical reaction parameter improves the temperature and mass transfer rate. The consistency of the results is affirmed by the correlation with results arising in the literature.